2021
DOI: 10.18502/ijrm.v19i1.8178
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of hesperetin on the quality of sperm, apoptosis, lipid peroxidation, and oxidative stress during the process of cryopreservation: An experimental study

Abstract: Background: Hesperetin is a bioflavonoid compound, largely used in Chinese traditional medicine and found plenty in citrus fruits. Hesperetin has beneficial effects against different diseases. The sperm cryopreservation process is a common method that is used in infertility laboratories. It has been reported that during the cryopreservation process, the quality of sperm is significantly reduced. Objective: To investigate the effect of hesperetin on the quality of human spermatozoa during the cryopreserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 44 publications
2
11
2
Order By: Relevance
“…Contrary to our findings, [U]. Valipour et al [28]. showed that the level of ROS formation increased during the freeze-thawing process, and 20 μM HSP treatment significantly reduced ROS levels.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to our findings, [U]. Valipour et al [28]. showed that the level of ROS formation increased during the freeze-thawing process, and 20 μM HSP treatment significantly reduced ROS levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Samie et al [27] reported that the dose of HSP (50 mg/kg/day) administered to rats contributed to an increase in sperm counts and motility. In another study, 20 µM hesperidin treatment during the cryopreservation of human sperm significantly improved the motility and morphology ratios of spermatozoa after cryopreservation [28]. Aksu et al [29] also showed that the application of HSP (300 mg/kg/day) for 7 days against reproductive damage in male rats caused an increase in the percentage of total sperm motility.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Then, 100 µL of the stock solution was mixed with 900 µL distilled water (100 µM Hesp solution). Finally, 10 and 20 µL of 100 µM Hesp solution were dissolved with 90 and 80 µL pre-extender sperm solution, respectively, and 1 and 2 µM Hesp solutions were prepared (Ali et al, 2021;Valipour et al, 2021). Hesp supplementation was performed according to the one-and two-step dilution protocols separately.…”
Section: Preparation Of Hesp Different Dosagesmentioning
confidence: 99%